System of supporting decision-making corporations at the regional level of management - Eliseeva, N. A.; Poddubnaya, E. V. (Radio Industry (Russia), 2018)
The article presents the concept of solving the actual scientific and practical problem – the development of a decision support system at the regional management level using new methods, models, algorithms and software tools that improve the efficiency of decision-making in the support of the strategic planning process. Leading decisions and initial principles that reflect the laws of development and management of regional corporations, the principles of their social management are considered. The organizational structure of the corporation economic and social system management is shown. The main characteristics that satisfy the developed decision support system are determined. The mathematical model of processing the collective expert estimations of the factors of tabular methods of the strategic analysis is considered. The components of the decision support system are determined. The proposed original concept of building a system to support strategic decision making allows increasing the efficiency and transparency of the stages of strategic regional planning for corporations and simplifying the procedures for strategic analysis and budgeting of investment programs.